Synthesis, Characterization, Antimicrobial and Time Killing Activities of New Sulfa-Derived Schiff Bases Coordinated with Cu(II) - Önder İdil; Hakan Şahal; Erdal Canpolat; Mustafa Özkan (Indonesian Journal of Chemistry, 2023)
Synthesis of three Schiff bases of 5-bromo-3-nitro salicylaldehyde containing different sulfonamide group antibiotic compounds and their Cu(II) complexes was carried out. Structures of all compounds were characterized with spectroscopic methods, including Fourier transform infrared, proton nuclear magnetic resonance, and elemental analysis. The in vitro antimicrobial activity of ligands and complexes against Gram-negative and Gram-positive bacteria and the yeast Candida albicans was evaluated. It was determined that the ligand and complexes showed outstanding antimicrobial activity against almost all of the microorganisms tested. It has been observed that the newly synthesized complexes have more antimicrobial effects than the corresponding ligands. It has been determined that the newly synthesized complexes have more antimicrobial effects than the others (E. coli, L. monocytogenes, and C. albicans), especially on Staphylococcus aureus and Pseudomonas aeruginosa.